Impresión 3D como Herramienta Didáctica para la Enseñanza de Algunos Conceptos de Ingeniería y Diseño - Rua Ramirez, Edwin Blasnilo; Jimenez Diaz, Fernando; Gutierrez Arias, German Andres; Villamizar, Nelson Iván (Ingeniería, 2018)
Context: 3D printing can be used for a wide range of tasks such as the design and testing of prototypes and finished products in a shorter time. In mechanical engineering, prototype designs are continuously generated in academic class activities and final coursework projects by students and teachers. However, students show limitations while understanding the abstract concepts represented with such designs. Method: Firstly, a large scale 3D printer with improved technical specifications compared to traditional market options and similar price, was fabricated. By means of free software and hardware tools and easy-to-obtain alternative manufacturing materials, it was possible to decrease its manufacturing and operating costs. Then a set of study cases utilising the 3D printer in three different subject classes were designed and tested with two cohorts of students of Mechanical Engineering programme. Results: It was feasible to fabricate a cost-effective and practical 3D printer for constructing prototypes and pieces that benefit teaching and learning concepts in engineering and design areas. The experiments carried out in three subjects of engineering courses with second-year students, showed a similar trend of improving the average course grades, as it was observed in two cohorts in different terms. Conclusions: This type of low cost 3D printer obtained academic advantages as a didactic tool for the learning process in engineering and design subjects. Future work will consider applying this tool to other courses and subjects to further evaluate its convenience and effectivity.